1998
DOI: 10.1159/000021634
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of Ravenala madagascariensis and Parkia madagascariensis by Eulemur macaco in Madagascar

Abstract: Primates are known to be important in dispersal of seeds of tropical rainforest trees, but their role in pollination is very poorly documented. Although the ‘traveller’s palm’ Ravenala madagascariensis is widespread, only a single well-documented report exists for its pollination by Malagasy prosimians. Black lemurs, Eulemur macaco, exploit nectaries of Parkia as well as Ravenala systematically at the massifs of Ambato and Lokobe, and almost certainly contribute substantially to their pollination, confirming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…3B, C) [Sterling & McCreless, 2006]. The potential for coevolution between aye-ayes and the traveler's tree has long been recognized [Kress et al, 1994], yet the role of blue as a facultative color stimulus during lemur-plant interactions has received little attention [Sussman & Raven, 1978;Birkinshaw & Colquhoun, 1998]. …”
Section: Why Aye-ayes See Bluementioning
confidence: 99%
“…3B, C) [Sterling & McCreless, 2006]. The potential for coevolution between aye-ayes and the traveler's tree has long been recognized [Kress et al, 1994], yet the role of blue as a facultative color stimulus during lemur-plant interactions has received little attention [Sussman & Raven, 1978;Birkinshaw & Colquhoun, 1998]. …”
Section: Why Aye-ayes See Bluementioning
confidence: 99%
“…Garber (1988) and Riba-Hernández & Stoner (2005) found that adult individuals of Ateles geoffroyi, Saguinus mystax, and S. fuscicollis destroy the flowers of Symphonia globulifera (Guttiferae) when they were feeding on nectar. (Janson et al, 1981;Torres de Assumpção, 1981;Ferrari & Strier, 1992;Birkinshaw & Colquhoun, 1998) found that animals did not eat or caused little damage to the flowers when they were feeding on nectar.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we observed effective seed production in the three G. robusta trees used by the howlers. Other non-human primates appear to be involved in pollination, i.e Aotus lemurinus (Marín-Gómez, 2008), B. arachnoides (Torres de Assumpção, 1981), C. apella (Torres de Assumpção, 1981), and E. macaco (Birkinshaw & Colquhoun, 1998).…”
Section: In Contrast Studies On Aotus Trivirgatus Ateles Paniscus mentioning
confidence: 99%
See 1 more Smart Citation
“…Regular cathemeral activity, defined by significant amounts of activity during both the dark and light phases of the 24-hr cycle [Tattersall, 1987], has been described for Aotus azarae [Wright, 1989] and the lemur genera Eulemur [Tattersall & Sussman, 1975;Sussman & Tattersall, 1976;Tattersall, 1977Tattersall, , 1979Overdorff, 1988, Wilson et al, 1989Colquhoun, 1993Colquhoun, , 1998Overdorff & Rasmussen, 1995;Andrews & Birkinshaw, 1998;Birkinshaw & Colquhoun, 1998;Curtis et al, 1999;Donati et al, 1999;Rasmussen, 1999] and Hapalemur [Mutschler, 1999]. Observations of cathemeral activity in Hapalemur simus, Varecia variegata variegata [Wright, 1999] and the anthropoid Alouatta pigra [Dahl & Hemingway, 1988] were also reported.…”
Section: Introductionmentioning
confidence: 99%